Risk Factors for Hepatitis E Virus Infection and Eating Habits in Kidney Transplant Recipients - Eva Wu; Nadine Koch; Friederike Bachmann; Marten Schulz; Evelyn Seelow; Ulrike Weber; Johannes Waiser; Fabian Halleck; Mirko Faber; Claus-Thomas Bock; Kai-Uwe Eckardt; Klemens Budde; et al. (Pathogens, 2023)
There is a significant risk for ongoing and treatment-resistant courses of hepatitis E virus (HEV) infection in patients after solid organ transplantation. The aim of this study was to identify risk factors for the development of hepatitis E, including the dietary habits of patients. We conducted a retrospective single-center study with 59 adult kidney and combined kidney transplant recipients who were diagnosed with HEV infection between 2013 and 2020. The outcomes of HEV infections were analyzed during a median follow-up of 4.3 years. Patients were compared with a control cohort of 251 transplant patients with elevated liver enzymes but without evidence of an HEV infection. Patients’ alimentary exposures during the time before disease onset or diagnosis were assessed. Previous intense immunosuppression, especially treatment with high-dose steroids and rituximab, was a significant risk factor to acquire hepatitis E after solid organ transplantation. Only 11 out of 59 (18.6%) patients reached remission without further ribavirin (RBV) treatment. A total of 48 patients were treated with RBV, of which 19 patients (39.6%) had either viral rebounds after the end of treatment or did not reach viral clearance at all. Higher age (>60 years) and a BMI ≤ 20 kg/m2 were risk factors for RBV treatment failure. Deterioration in kidney function with a drop in eGFR (p = 0.046) and a rise in proteinuria was more common in patients with persistent hepatitis E viremia. HEV infection was associated with the consumption of undercooked pork or pork products prior to infection. Patients also reported processing raw meat with bare hands at home more frequently than the controls. Overall, we showed that the intensity of immunosuppression, higher age, a low BMI and the consumption of undercooked pork meat correlated with the development of hepatitis E.